Pengaruh Kualitas Atraksi Wisata Terhadap Kepuasan dan Motivasi Kunjungan kembali Wisatawan Mancanegara di Kawasan Wisata Tanjung Bira, Kabupaten Bulukumba - Achmad Gani, Pratiwi Juniar (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
Condition of tourism area in The Tanjung Bira, Bulukumba have many potential attraction for visited by tourist but its not accompanied with development of tourist attraction. This was shown when negative image make tourism area in Tanjung Bira became have a low quality which is not accompanied by an increase in the number of visits from year to year in there. By improving the quality of tourism attraction is expected to increase the satisfaction and motivation to come back so that it can give a direct effect on the tourism area. This research aims to discover how the quality of the tourist attractions that are available can show its ability to influence the satisfaction and motivation of return visits by foreign tourists. The research method used in this research is descriptive quantitative and qualitative aims to explore, search for meaning, the facts and the proper interpretation of the phenomenon or behavior tendencies of tourists in conducting tourism activities in the Tanjung Bira. Perception, the satisfaction of tourists and tourist attraction is the key to understanding the behavior and motivation of return visit of tourists. The results of this research were (1) tourism are in Tanjung Bira has a quality tourist attraction is not good enough so (2) did not gave optimal satisfaction to foreign tourists in conducting the tour (3) Which then gave affect the motivation level of return visits by foreign tourists where only motivated to made his first visit not for the next visit.